ڕۆڵى ڕێکەوتنامەى سایکس پیکۆ لە قوڵکردنەوەى نامۆبوونى خودى کوردیدا - قادر, كامه‌ران محمد (Sulaimani Journal for Humanities, 2018)
Abstract It is considered that Alienation from the mental and social lesions, which is elaborated through different styles, as a painful isolation, or discontinuity, or fragmentation which disconnect belonging things from each other. For instance, people will alienate from the political process when they think that they are disconnected from it, and they feel powerless over the political system. The Alienation of Kurdish people’s personality linked to historical events. That personality was born in a compulsory environment, uncivilized and a distorted social structure. The Alienation has participated in events, which its impacts were catastrophic for the Kurdish people, and then it is considered to be an essential factor through which the historian can discover unknown world and a numbers of the historical secrets. The research has adopted the analytical methods in three kinds of Alienation, in which the Sykes - Picot agreement has deepened in the Kurdish people’s personality.